2015
DOI: 10.1007/s11356-015-5987-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth, photosynthesis, and defense mechanism of antimony (Sb)-contaminated Boehmeria nivea L.

Abstract: Ramie (Boehmeria nivea L.) is the oldest cash fiber crop in China and is widely grown in antimony (Sb) mining areas. To evaluate the extent of Sb resistance and tolerance, the growth, tolerance index (TI), Sb content in plant parts and in Hoagland solution, bioaccumulation factor (BF), photosynthesis, and physiological changes in Sb-contaminated B. nivea (20, 40, 80, and 200 mg L(-1) Sb) grown hydroponically were investigated. The Sb tolerance and resistance of ramie were clearly revealed by growth inhibition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…These findings are similar to the results described by Pan et al [ 19 ] for maize, and are characteristic symptoms of heavy metal toxicity [ 67 , 68 ]. Also observed was preferential accumulation of the absorbed Sb in the roots, consistent with very low TF values in non-Sb-accumulating plants [ 42 , 44 , 65 , 69 ]. This reduced root development may be due to an alteration in the elongation of the cells located in the root elongation zone, as can be seen in the longitudinal fluorescence microscopy images (data no show).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…These findings are similar to the results described by Pan et al [ 19 ] for maize, and are characteristic symptoms of heavy metal toxicity [ 67 , 68 ]. Also observed was preferential accumulation of the absorbed Sb in the roots, consistent with very low TF values in non-Sb-accumulating plants [ 42 , 44 , 65 , 69 ]. This reduced root development may be due to an alteration in the elongation of the cells located in the root elongation zone, as can be seen in the longitudinal fluorescence microscopy images (data no show).…”
Section: Discussionmentioning
confidence: 55%
“…Also, Feng et al [ 81 ] and Zayneb et al [ 72 ] obtained higher lipid peroxidation levels despite of the increased antioxidant activity in response to other heavy metals. On the contrary, Chai et al [ 65 ] obtained results that show sharp declines in SOD, peroxidase and catalase activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSII was confirmed as an important site of photoinhibition, but its light use efficiency can be reduced by drought/flooding, heavy metals, saline or other stress factors, and there by the plants were injured by photoinhibition. As reported, the chlorophyll fluorescence parameters of Ramie ( Boehmeria nivea L.) including F v /F m and Φ PSII were not significantly changed under Sb stress (20–200 mg⋅L -1 ) (Chai et al, 2016), but were significantly reduced under salty or drought stress (Huang et al, 2013). The maximum photochemical quantum yield (F v /F m ) of maize under Sb stress (50–1000 mg⋅kg -1 soil) declined (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 76%
“…In barley, activities of GS, GOGAT, and GDH in the root or leaf of plantlets increased with increasing N-content (0–2 mmol L -1 ) under hydroponic culture, and varieties with high NUE had higher GS, GOGAT, and GDH activities (Jawad et al, 2017). Fluorescence indicators, which are dramatically affected under biotic or abiotic stresses, are usually regarded as indicators of stress tolerance (Chai et al, 2016). It was reported that the chlorophyll content (Kumara and Bandara, 2001), photosynthesis (Meinzer and Zhu, 1998; Kumara and Bandara, 2001), maximal photochemical efficiency (Meinzer and Zhu, 1998), N content and biomass (Kumara and Bandara, 2001) decreased significantly in sugarcane under a low N supply.…”
Section: Discussionmentioning
confidence: 99%